(untitled) (Canadian Perspectives on Academic Integrity, 2023)
Academic integrity misconduct plagues higher education institutions, causing faculty to experience discouragement toward plagiarism prevention and detection (Doró, 2014; Thomas, 2017). While some faculty recognize a lack of knowledge about what constitutes plagiarism (Doró, 2014; Jeffrey & Dias, 2019), others cite the lack of communication of institutional policies in place (Thomas, 2017). Yet, research shows that an individual’s perception of a situation has a significant impact on their motivation and behaviors (Bandura, 2019; Weiner, 2001). From this perspective, if personal perception influences the spheres of someone’s work (Montgomery et al., 2010), it is pertinent to question the role played by his or her locus of control. This theoretical concept refers to a person’s beliefs of their control over life events and their outcomes, which could play in the prevention of plagiarism by College Teachers. During our presentation, we will expose the results of a content analysis based on 17 semi-structured interviews with College Teachers in the Canadian Province of Quebec. We will cover the perception of participants regarding their internal and external locus of control toward plagiarism situations occurring in their classrooms. Then, we will discuss how the COVID-19 pandemic, among other things, influenced the locus of control of participants. In addition to supplementing the knowledge around the concept of academic integrity, this presentation will provide avenues of exploration to better equip post-secondary educators to teach academic integrity.